Epileptic Adolescents and Ramadan Fasting: A Prospective Cohort Study - Darwish, Amira Hamed (Journal of Pediatric Neurology, 2020)
This study aimed to evaluate the effect of Ramadan fasting on seizure control in epileptic adolescents. A prospective cohort study that included 56 epileptic patients aged 11 to 18 years. Patients were followed-up in the pediatric neurology clinic at Tanta University Children's Hospital during Ramadan 2019. Seizures frequency and severity, measured by Chalfont seizure severity scale, during Ramadan fasting were compared with those in the month before Ramadan. Before Ramadan, 43/56 patients were controlled and seizure free. Meanwhile, 13/56 patients were uncontrolled and had seizure frequency of one to six seizures in the month before Ramadan. There was no significant difference in seizure frequency during Ramadan compared with before Ramadan (p = 0.132), whereas seizure severity was significantly reduced during Ramadan (p = 0.028). Both seizure frequency and severity were significantly lower during Ramadan in uncontrolled epileptic patients compared with before Ramadan (p = 0.02 and 0.005). Ramadan fasting is safe in adolescents with epilepsy. Fasting is not a precipitating factor for seizures in epileptic adolescents, provided compliance to antiepileptic drugs, and could be beneficial for seizure control in uncontrolled epilepsy.
Keywords: seizure control; fasting; epilepsy